ANALYSIS OF RAMADHAN EFFECT TOWARD MARKET RETURN AND TRADING VOLUME IN INDONESIA SHARI'AH COMPLIANCE INDEX - -, calvin (Jurnal Manajemen Update, 2020)
This research is an event study that aims to find out the effects arising from the month of Ramadan, on the Indonesian Sharia Stock Index on the Indonesia Stock Exchange for the period of 1435H to 1439H, using indicators of market returns and trading volume. This study uses secondary data in the form of daily stock index prices and daily trading volume of the Indonesian Sharia Stock Index (ISSI) with a total of 1186 days from 1435H to 1439H. The statistical test used to test the hypothesis is a non-parametric test, because the data used are not normally distributed. The results of the T-test on market returns between 1435H and 1439H are known that there is no significant difference in market return between the month of Ramadan and other month. The results of T-test on the trading volume between 1435H and 1439H, it was found that there were significant differences which meant the market responded to the event. The results of the study prove that market returns do not have significant differences due to the stable index value on Indonesian Islamic stocks. However, the trading volume has a significant difference.       Keywords: Ramadhan, Ramadhan Effect, Market Return, Trading Volume, Index of Indonesia Shari?ah Compliance